Influence Discipline And Environment Work On Employee Performance In Management Body Finance And Asset Mesuji District Area - Maksum, Maksum; Parela, Epi (Journal of Accounting and Management, 2025)
Employee performance is Wrong one factor that must be considered by organizations or government agencies in order to achieve their goals. An organization that has high discipline will certainly find it easier to achieve its goals because the applicable systems or rules can be implemented well by its employees. The next factor that must be considered is the work environment, both physical and non-physical. This study aims to determine the influence of work discipline and work environment on employee performance at the Regional Financial and Asset Management Agency of the Regency Mesuji. The type of research used in this study is quantitative field research , namely research that emphasizes its analysis on data in the form of numbers and the research examines... real life in the field in this case on the object being studied. This study used 44 research respondents. Based on data analysis has found answer the hypothesis is as follows; There is an influence of work discipline (X 1 ) on employee performance (Y), with level of influence by 21.9%. There is environmental influence work (X 2 ) on employee performance (Y) with an influence level of 27.1%. There is an influence of work discipline (X 1 ) and work environment (X 2 ) together on employee performance (Y) with an influence level of 42.7%.